DISTRIBUSI EKONOMI ISLAM DALAM PERSPEKTIF PENDIDIKAN QS. AL-ISRA’ AYAT 29-30 - Sugianto, Efendi (Tawshiyah: Jurnal Sosial Keagaman dan Pendidikan Islam, 2023)
Wealth can be produced in a country with large amounts, but if its distribution is not based on true and fair principles, then the country will not achieve prosperity. Islam  takes the  middle  path that  can help enforce a  fair and just system. Islam also does not give  everything,  nor unlimited rights in owning personal  weaith  for a person in the  field  of production,  nor  does it attract a  person  to an  economic  process system  that  under  this system he cannot obtain, and has wealth independently. how is the definition of distribution in Islamic economics in the educational  perspective Qs. Ai-lsra verses 29-30, and How is the  Mechanism in the  distribution of Islamic economy in the educational perspective Qs. Al-lsra verses 29-30. The study uses a descriptive analysis method, which is library research that provides a clear, objective, systematic, analysis of Islamic economic distribution in the educational perspective Qs. Ai-Isra verses 29-30. It can be drawn the common thread that distributing the economy or finances, a person is  prohibited  from applying miserly and in effect extravagant. but the best thing in distributing the economy  and  finance  is  to maintain the principle of balance and sufficiency. God who certainly expands or narrows the sustenance of a person, family, community, or nation and country; For Allah is Supra-Knowing, Supra--Seeing